Association between hypokalemia and cardiovascular diseases among hospitalized patients in tertiary care teaching hospital in North Karnataka: a retrospective study - Badiger, Raju H.; Desai, Santosh B.; Kantamanenin, Ravindra; Kavatkopp, Chetana K.; George, Joel; Basha, Sheikh H. (International Journal of Advances in Medicine, 2017)
Background: Potassium is an extremely crucial element in maintaining the normal charge between intracellular and extracellular space. Normal cellular function is maintained through potassium homeostasis. The normal range of plasma potassium is 3.5 to 5.1 mmol/L. The deviation both hypo and hyperkalaemia are associated with cardiovascular diseases especially cardiac arrhythmia. The objective was to study the association of hypokalaemia on cardiovascular diseases. Methods: During this one year of retrospective study socio-demographic profile of the patients were collected from the medical record section of hospital. The participants were grouped into four classes based on the serum potassium levels as, Group A: < 2 mmol/L, group B: 2-2.49 mmol/l, group C: 2.5 - 2.9 mmol/L, group D: 3 - 3.49 mmol/L and group E (control group) 3.5 to 5.1 mmol/L. The participants were also grouped as those suffering from cardiovascular diseases and those with non-cardiovascular diseases. Results: In our study 4818 records were categorized into 5 groups including control group. Males (61.35%) were slightly more than female (38.65%). The mean age group was 43±4 years. Results revealed that there was positive association between the sexes. Females were more commonly associated as compared to males. Hypokalaemia among cardiovascular diseases was only 22.2% as compared to non-cardiovascular diseases. The mean systolic (142±8) and diastolic Blood pressure (92±2) among cardiovascular diseases was slightly higher as compared with the non-cardiovascular diseases. Conclusions: Hypokalaemia is significantly associated with myocardial infarction when compared with other disorders. Hypokalaemia was more commonly associated with cardiovascular diseases as compared with non-cardiovascular diseases.